The Phenomenology and the Philosophy of Running: The Multiple Dimensions of Long-Distance Running - Koski, Tapio (Springer, 2015)
This book describes and analyzes the levels of experience that long-distance running produces. It looks at the kinds of experiences caused by long-distance running, the dimensions contained in these experiences, and their effects on the subjective life-world and well-being of an individual. Taking a philosophical approach, the analysis presented in this book is founded on Maurice Merleau-Ponty´s phenomenology of the body and Martin Heidegger´s fundamental ontology.